2012
DOI: 10.1136/bcr.01.2012.5673
|View full text |Cite
|
Sign up to set email alerts
|

Community acquired Pseudomonas pneumonia in an immune competent host

Abstract: Pseudomonas aeruginosa is an uncommon cause of community-acquired pneumonia in immune-competent hosts. It is commonly seen in patients with structural lung abnormality such as cystic fibrosis or in immune compromised hosts. Here, the authors report a case of community-acquired Pseudomonas pneumonia in a 26-year old healthy man who presented with 8-week history of malaise and cough.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…Repeated sputum for gram stain and bacterial culture were sterile, sputum smears for Ziehl-Neelsen staining were negative for acid fast organisms, and sputum for fungal culture showed insignificant growth. We reviewed the literature for cavitatory lesions in immunodeficient individuals, and found that pneumonia is typically caused by Staphylococcus aureus [3] or Pseudomonas aeruginosa [4], and Mycobacterium tuberculosis [5–7] is rarely reported with Rhodococcus equi [810] and Nocardia asteroids [1117]. …”
Section: Discussionmentioning
confidence: 99%
“…Repeated sputum for gram stain and bacterial culture were sterile, sputum smears for Ziehl-Neelsen staining were negative for acid fast organisms, and sputum for fungal culture showed insignificant growth. We reviewed the literature for cavitatory lesions in immunodeficient individuals, and found that pneumonia is typically caused by Staphylococcus aureus [3] or Pseudomonas aeruginosa [4], and Mycobacterium tuberculosis [5–7] is rarely reported with Rhodococcus equi [810] and Nocardia asteroids [1117]. …”
Section: Discussionmentioning
confidence: 99%
“…Pseudomonas aeruginosa is a common nosocomial pathogen that often causes pneumonia in hospitalized patients [1,2] , most of whom have underlying medical conditions or risk factors for Pseudomonas infection. Although rare, case reports and reviews have described healthy individuals who have developed community-acquired pneumonia (CAP) caused by P. aeruginosa [3–8] that is often rapidly progressive and fatal.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, we found 13 cases of necrotizing CAP due to P. aeruginosa associated with cavitation. Table 1 summarizes the 11 most recent cases [[1], [2], [3], [4], [5], [6], [7], [8], [9], [10]]. The main risk factors for necrotizing CAP due to P. aeruginosa are: lung structural abnormalities (including cystic fibrosis, emphysema, bronchial dilatation, chronic obstructive pulmonary disease), immunocompromised condition (including neoplasia, neutropenia, prolonged antibacterial therapy, immunosuppression), and exposure to contaminated liquids (including hot tub, spa, humidifier) [1,2].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding antimicrobial management for CAP, the literature is summarized in Table 1 [[1], [2], [3], [4], [5], [6], [7], [8], [9], [10]]. It is generally not appropriate to administer empiric anti-Pseudomonas therapy.…”
Section: Discussionmentioning
confidence: 99%